2021
DOI: 10.1002/ijgo.13962
|View full text |Cite
|
Sign up to set email alerts
|

Chronic endometritis: A prevalent yet poorly understood entity

Abstract: Objective To examine the prevalent understanding of and management approaches to chronic endometritis among obstetricians/gynecologists. Methods In a cross‐sectional observational study, 262 members of national and international professional obstetrician/gynecologist societies were surveyed via anonymous electronic survey that investigated knowledge of the pathophysiology, diagnostic criteria, clinical implications, and treatment strategies for chronic endometritis. Statistical analyses of results were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…At last, Considering the absence of a clear understanding of chronic endometritis diagnosis, we still need to further explore the diagnostic criteria of endometritis to facilitate the management and treatment of patients. 36 , 37 …”
Section: Discussionmentioning
confidence: 99%
“…At last, Considering the absence of a clear understanding of chronic endometritis diagnosis, we still need to further explore the diagnostic criteria of endometritis to facilitate the management and treatment of patients. 36 , 37 …”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the Human Microbiome Project (HMP) has found that about 9% of human microbiota exists in female genital tract ( Margulies et al., 2022 ). In the past, it was believed that female genital tract microorganisms only inhabit the vagina, vulva, anus and so on.…”
Section: Introductionmentioning
confidence: 99%
“…These low abundance microbiota constitute the intrauterine microecology. Many studies, including HMP, have found the importance of microorganisms and their genomes in human health and disease ( Chen et al., 2017 ; Margulies et al., 2022 ). So we boldly speculate that chronic endometritis (CE), endometrial polyps (EP), and even endometrial cancer may occur when the microbiota in the uterus changes or pathogens invade.…”
Section: Introductionmentioning
confidence: 99%
“…There is still no consensus regarding the clinical significance of CE, with no definitive evidence to support the hypothesis that CE is always associated with adverse reproductive outcomes ( 9 , 10 ). The higher prevalence of CE in patients with recurrent implantation failure (RIF), recurrent pregnancy loss (RPL), and preterm delivery, however, does support the belief that CE may adversely affect some reproductive outcomes in IVF ( 11 ).…”
Section: Introductionmentioning
confidence: 99%